The effectiveness of ergo- and psychotherapy in the process of sanatorium-resort treatment of spinal patients - Mikhaylenko, V.; Fedorchenko, R. A.; Komissarova, O.; Plakida, A.; Михайленко, В.; Федорченко, Руслана Анатоліївна; Комісарова, О.; Плакіда, А. (My University, 2020)
The aim is to explore the possibilities of improving motor and sensitive disorders to ensure the highest possible social adaptation - the expansion of self-service skills, opportunities for affordable employment, or the restoration of professional activity flax. Methods: To study the possibilities of improving the social reintegration of patients during rehabilitation in a mud resort, we observed 240 patients who had an injury to the cervical spine 24 years. Disease duration ranged before 3 years, 4-7 years, more 7 years. We studied the occupational therapy method and group psychotherapy method. All patients were divided into three representative groups: 91 patients (group 1) received a course of balneoplasty therapy in the form of mud applications on the spine and lower limbs at a temperature 42-44 0 C, exposure time 20 min, placement of procedures - every other day, for a total of 12-15 procedures per treatment; on days free of mud cure, hydrokinesitherapy was performed in a pool with warm (29-32 0 С) brine water, 12-15 procedures, and also apparatus physiotherapy procedures, massage and exercise therapy. In addition to the course of balneopedotherapy, 149 patients also received ergo-therapy and psychotherapy (90 people - group 2) and only occupational therapy - 59 people (group 3). Results: Improvement of post-traumatic organic neurological disorders caused by balneo-mud therapy creates a favorable basis for conducting training activities that expand patients’ functionality. The inclusion of ergotherapy in the rehabilitation process of spinal patients in a balneo-mud resort is appropriate and justified. It allows not only to expand the functionality of patients but also to reduce the time to master the essential self-care skills and consolidate them. Conclusion: The inclusion of psychotherapy in the complex of occupational therapy is desirable. It allows you to influence the psycho-emotional state of the patient and improve the effectiveness of training activities, especially in male patients. Changing the hospital and closed home atmosphere to the conditions of the resort, the possibility of broad communication, participation in various social events significantly change the psycho-emotional state of patients, increasing their activity, causing an increase in the setting for inclusion inactive life.
Keywords: ergotherapy; psychotherapy; spinal injuries; activity and participation; rehabilitation; social adaptation